Analysis of Students' Learning Difficulties in Islamic Religious Education (PAI): A Case Study at SMP Rahmat Islamiyah Medan - Kiftya, Meilan; Giansyah, Rizky; Fauziah, Silvi; Nurjanah, Hayin (Yayasan Rahmat Islamiyah, 2025)
This study aims to analyze the learning difficulties experienced by students in Islamic Religious Education (PAI) at SMP Rahmat Islamiyah Medan. The research method used is a qualitative approach with a case study, involving in-depth interviews with students, teachers, and other related parties. The findings of the study reveal that the main factors causing learning difficulties in PAI are the students' lack of understanding of the material, limited proficiency in Arabic, and low motivation to learn. The study also identifies various strategies used by teachers to address these difficulties, including the use of more interactive methods and a contextual approach to religious values.